INTERNAL CONTROL MODERATES THE INFLUENCE OF THE FRAUD HEXAGON ON FINANCIAL STATEMENT FRAUD - Dina Indriana; Muslich Anshori (Berkala Akuntansi dan Keuangan Indonesia, 2022)
The focus of the research is to investigate internal control in moderating the effect of variables on the elements of The Fraud Hexagon on fraudulent financial reporting. The sample was selected using purposive sampling at public companies in the construction industry in Indonesia for the period 2016 – 2020. The research hypothesis was tested using Multiple Linear Regression Analysis with SPSS. The results of the study indicate that audit fee have a negative effect on financial statement fraud because low audit fees make auditors not give greater effort to the audit process so that the risk of audit quality is getting lower. Low audit quality makes fraudsters believe that their behavior will not be detected, thereby increasing the possibility of financial statement fraud. Meanwhile, internal control will not work effectively if employees do not have the same perception as the company regarding internal control.